Populism and natural resources - Forlani, Nicolas (Universidad Nacional de Villa María, 2018)
In the present work we compare the three classic Latin American populist experiences, namely Lazaro Cardenas' governments in Mexico (1934-1940), Juan Domingo Perón in Argentina (1945-1955) and Getulio Vargas in Brazil (1951-1954); In the light of its policies on natural resources. The article begins with a brief reference around the theoretical debates that ignites the concept of populism as well as the contemporary discussions in relation to the notion of natural resources. Then the comparison of the three political experiences referred to is carried out taking as analysis variables the policies of these governments in relation to natural resources in general and oil and land in particular.